Physico-chemical changes and kinetics for mineralisation of EFB composting - Sim, Vivienne Jie Wei (Curtin University, 2015)
Composting is a biochemical process, highly dependent on temperature and aeration rate. This research aims at studying the mineral dynamics, developing an empirical model and optimising the composting of EFB. Mineralisation of nitrogen, phosphorus, potassium and calcium were found to be affected by both variables. Optimisation of the process shows the highest yield of nitrogen (1.86%) can be obtained at a temperature of 41.5°C and aeration rate of 0.37L/min.kg, over composting period of 42 days.